2020
DOI: 10.3390/nano10050981
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of ZnO on Mesoporous Silica: Insights into Growth Behavior of ZnO via In-Situ Thermogravimetric Analysis

Abstract: ZnO is a remarkable material with many applications in electronics and catalysis. Atomic layer deposition (ALD) of ZnO on flat substrates is an industrially applied and well-known process. Various studies describe the growth of ZnO layers on flat substrates. However, the growth characteristics and reaction mechanisms of atomic layer deposition of ZnO on mesoporous powders have not been well studied. This study investigates the ZnO ALD process based on diethylzinc (DEZn) and water with silica powder as substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
4
17
0
Order By: Relevance
“…An in-situ gravimetric study of the growth behaviour of ZnO on SiO 2 is reported elsewhere. 37 In the ZnO ALD process,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An in-situ gravimetric study of the growth behaviour of ZnO on SiO 2 is reported elsewhere. 37 In the ZnO ALD process,…”
Section: Resultsmentioning
confidence: 99%
“…Details and descriptions are given elsewhere. 37 Therefore, to the best of our knowledge, this study is the first study that uses ALD of ZnO to synthesize in a controlled way a bimetallic PtZn nanoalloy catalyst for dehydrogenation of alkanes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…% Zn). 63 As for Al, the Zn surface concentration can be calculated and correlated with the surface hydroxyl group density. For the DEZ deposition at 80 ○ C, the Zn concentration is 2.1 Zn/nm 2 and with that only 63% of the OH groups might be covered.…”
Section: B Parallel Depositionmentioning
confidence: 99%
“…The unique assets of ALD have attracted the attention of ALDgrown ZnO films for various applications. For example, the excellent conformality enables the deposition of ZnO on high surface area powders used in catalysis [8]. Doped ZnO can be used as transparent conductive oxide (TCO) for optoelectronics [9] and ZnO can be deposited at near room temperature [6,[10][11][12][13], making ALD a suitable deposition method for temperaturesensitive substrates such as polymers.…”
Section: Introductionmentioning
confidence: 99%